Validitas dan praktikalitas LKPD berbasis strategi scaffolding pada materi pengukuran dan vektor untuk kelas X SMA/MA - Miftahul Jannah; Amali Putra; Hufri Hufri; Wahyuni Satria Dewi; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2019)
One of the goals of learning is that students' cognitive abilities increase. In an effort to improve cognitive abilities, there are times when students need to get guidance so that their thinking skills increase from the average ability they have. One form of guidance is the scaffolding strategy. This study aims to overcome these problems by producing student worksheets based on scaffolding strategies to improve cognitive abilities, and determine their worth in terms of validity and practicality. This research was conducted in class X SMAN 2 Pariaman in odd semester 2019/2020. This research is a type of research and development (R & D) using the 4D development model which is reduced to 3D (define, design and development). The student worksheet developed involved 5 validators and 2 physics teachers as practitioners and 1 class to test practicality. Instruments of validity and practicality are used after going through discussions with the validator with indicators of development goals. The analysis technique used in this research is quantitative analysis using the moment kappa formula. The results obtained from the feasibility test and practicality of scaffolding-based LKPD based on validator assessment are categorized as valid, with an average value of kappa moment of 0.85 in the very high category. Based on practitioners' assessment, it is categorized as practical with an average kappa moment of 0.89 by teachers and 0.74 by students. So that scaffolding-based LKPD can be said to be valid and practically used in high school physics class X learning.